2015
DOI: 10.1038/onc.2015.21
|View full text |Cite
|
Sign up to set email alerts
|

TRIM25 has a dual function in the p53/Mdm2 circuit

Abstract: P53 is an important tumor suppressor that, upon activation, induces growth arrest and cell death. Control of p53 is thus of prime importance for proliferating cells, but also for cancer therapy, where p53 activity contributes to the eradication of tumors. Mdm2 functionally inhibits p53 and targets the tumor suppressor protein for degradation. In a genetic screen, we identified TRIM25 as a novel regulator of p53 and Mdm2. TRIM25 increased p53 and Mdm2 abundance by inhibiting their ubiquitination and degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 28 publications
2
62
1
Order By: Relevance
“…For example, Morris and colleagues showed that liver-specific deletion of p53 results in liver cancer (both HCC and cholangiocarcinomas) in about 41% of mice at 10 months, along with increased transforming growth factor-beta levels [24]. It is noteworthy that the expression levels of p53 are regulated by various E3 ubiquitin ligases, including TRIM proteins, such as TRIM25 and TRIM59 [25,26]. In the present study, we showed that TRIM11 similarly decreased the expression levels of p53 and regulated its downstream molecules in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Morris and colleagues showed that liver-specific deletion of p53 results in liver cancer (both HCC and cholangiocarcinomas) in about 41% of mice at 10 months, along with increased transforming growth factor-beta levels [24]. It is noteworthy that the expression levels of p53 are regulated by various E3 ubiquitin ligases, including TRIM proteins, such as TRIM25 and TRIM59 [25,26]. In the present study, we showed that TRIM11 similarly decreased the expression levels of p53 and regulated its downstream molecules in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Let-7 preE serves as a platform to recruit RNA-binding proteins such as LIN28, KHSRP (also known as KSRP), hnRNPA1 and TRIM25, in order to posttranscriptionally regulate let-7 biogenesis(Heo et al, 2008; Michlewski and Caceres, 2010; Newman et al, 2008; Rybak et al, 2008; Trabucchi et al, 2009; Viswanathan et al, 2008; Zhang et al, 2015). LIN28 proteins play pervasive roles during animal development and are often dysregulated in cancer(Ambros and Horvitz, 1984; Moss et al, 1997; Moss and Tang, 2003; Shyh-Chang and Daley, 2013; Thornton and Gregory, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, TRIM24 (Allton et al, 2009), TRIM39 (Zhang et al, 2012a,b) and TRIM59 (Zhou et al, 2014) help to degrade p53. In addition, TRIM8, TRIM13, TRIM19, TRIM21 and TRIM25 also affect p53 stability (Bernardi et al, 2004;Joo et al, 2011;Caratozzolo et al, 2012;Reddy et al, 2014;Zhang et al, 2015). TRIM28, TRIM29 and TRIM32 antagonize p53 function (Wang et al, 2005;Yuan et al, 2010;Liu et al, 2014).…”
Section: Role Of Trim-directed Precision Autophagy In Diseasementioning
confidence: 99%